A double-closed wedge broken-line osteotomy for cubitus varus deformity. Issue 23 (11th June 2021) - You, Chao; Zhou, Yibiao; Han, Jingming
Abstract : Abstract: Various osteotomy methods have been proposed in the treatment of cubitus varus. We designed an improved stepped osteotomy to achieve improved deformity correction. We refer to this new approach as double-closed wedge broken-line osteotomy and report a series of clinical and imaging results (deformity correction, range of motion [ROM], function, osteotomy healing, and complications) of patients with cubitus varus treated with this technique. Between July 2014 and July 2019, we treated 9 cases of cubitus varus using the new technique. The study was conducted in accordance with the principles of the Declaration of Helsinki, and the study protocol was approved by the ethics committee of Shenzhen Children's Hospital. We obtained written parental consent for the minors before the study was begun. We compared preoperative and postoperative clinical and imaging parameters (humeral elbow-wrist angle, elbow ROM) in all patients. Postoperative evaluation was performed by telephone interview and outpatient review. The median follow-up was 23.2 months (range, 3–63 months). The median humeral elbow-wrist angle modified from −14.27 to 15.15. The median clinical and imaging parameters after correction of deformity were not different from that of the normal side. Using our rehabilitation program, all patients recovered preoperative elbow ROM at the last follow-up. Our double-closed wedge broken-line osteotomy has a larger cancellous bone contact surface. The deformity correction is satisfactory, the osteotomy healing is reliable, and the incidence of complications is low. Level of Evidence: Level IV.